Pengaruh Kebisingan Terhadap Kelelahan Kerja Pada Tenaga Kerja di Bagian Persiapan PT. Iskandar Indah Printing Textile Surakarta - PUTRI, ANINDYA NUARI (2011)
PT. Iskandar IndahPrinting Textile represent the peripatetic company is jacquards area. This company have hence its noisy modern machine exceed the value float the boundary ( NAB) 85 dBA. Noise exceeding NAB can cause the fatigue for labour which incured during 8 clock one day. So that this research target to know the noise influence tiredly labour in shares process the winding and process the ricing. This research use the analytic research observasional type, by using desain cross sectional. Sampling technique used by is purposive of sampling and quota sampling meaning determination sampel fulfilling conditions till fulfill the amount specified. From statistical test result [of] independent test between]\ fatigue before job and hereafter work shares process the winding and part of process ricing got result signifikan 0,023 or p > 0,05 by t-count 2,365. From result of inferential solution and research hence it is true that there influence which signifikan between noise tiredly [worker part of process winding exceeding NAB ( 85 dBA). Suggestion given Give the training and counselling to labour about noisy effect health trouble so that during working always hence appliance of protector of ear or earplug.